A Two-Dimensional Landau-Lifshitz Model in Studying Thin Film Micromagnetics - Jingna Li (Abstract and Applied Analysis)
The paper is concerned with a two-dimensional Landau-Lifshitz equation which was first raised by A. DeSimone and F. Otto, and so fourth, when studying thin film micromagnetics. We get the existence of a local weak solution by approximating it with a higher-order equation. Penalty approximation and semigroup theory are employed to deal with the higher-order equation.